Is laser surface texturing good or bad for rolling element bearings? - Yonggang Meng (Friction)
Abstract A short commentary on the two research articles published in Friction in 2021 is presented. Both articles reported experimental results of applications of laser surface texturing technology to the raceway of rolling element bearings. After briefly reviewing the main findings of the articles, the arguable problems and distinctions between the two articles are pointed out.